2019
DOI: 10.1093/rheumatology/kez374
|View full text |Cite|
|
Sign up to set email alerts
|

Progression of nailfold capillaroscopic patterns and correlation with organ involvement in systemic sclerosis: a 12 year study

Abstract: Objective The aim of this observational study was to investigate the evolution of scleroderma microangiopathy throughout different nailfold videocapillaroscopy (NVC) patterns (‘early’, ‘active’, ‘late’) as well as the prevalence of organ involvement in SSc patients during a 12-year follow-up. Methods Thirty-four SSc patients showing at baseline (first capillaroscopic analysis) the ‘early’ NVC pattern of microangiopathy were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 49 publications
1
27
2
Order By: Relevance
“…However, the progressive systemic fibrosis in ILD positive patients was also confirmed by the concomitant presence of the most advanced “Late” NVC pattern of microvascular damage that characterizes SSc patients with intensive fibrosis [ 26 ]. Based on these clinical considerations, the downregulatory effect of nintedanib on the transition of fibrocytes isolated from Scl70 + ILD + patients into myofibroblasts and their ECM overproduction might be a further supporting element for the beneficial effects exerted by nintedanib in reducing the progression of the ILD in SSc [ 15 , 16 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the progressive systemic fibrosis in ILD positive patients was also confirmed by the concomitant presence of the most advanced “Late” NVC pattern of microvascular damage that characterizes SSc patients with intensive fibrosis [ 26 ]. Based on these clinical considerations, the downregulatory effect of nintedanib on the transition of fibrocytes isolated from Scl70 + ILD + patients into myofibroblasts and their ECM overproduction might be a further supporting element for the beneficial effects exerted by nintedanib in reducing the progression of the ILD in SSc [ 15 , 16 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microvasculopathy represents a fundamental part of SSc pathogenesis, leading to several clinical manifestations such as Raynaud's phenomenon and digital ulcers [45]. Multiple cohort studies have postulated that nailfold capillaroscopic abnormalities correlate with the severity of organ involvement including PAH [13,41,42,46]. Indeed, in a 3-year longitudinal study, progressive loss of capillaries, presence of angiogenesis, and late scleroderma pattern were identified as markers for the occurrence of PAH [42].…”
Section: Discussionmentioning
confidence: 99%
“…SSc-PAH has also been associated with higher scores for capillary loss and capillary disorganization [41]. Additionally, it has been reported that increasing echocardiographically derived systolic pulmonary arterial pressure correlates with the severity of scleroderma pattern [46]. Furthermore, a diagnostic accuracy meta-analysis assessing the value of NVC in the diagnosis of SSc-PAH demonstrated that lower capillary density and increased capillary loop width could potentially detect patients with SSc-PAH [18].…”
Section: Discussionmentioning
confidence: 99%
“…NVC is to date the best tool to analyze microvascular abnormalities in CTDs [ 17 , 18 ]. Additionally, NVC alterations in course of SSc are well-defined and correlate with organ involvement and disease progression, in contrast to other CTDs—such as in SLE, SjS, MCTD, and IIM—in which NVC alteration is less disease-specific [ 19 24 ].…”
Section: Discussionmentioning
confidence: 99%